The Influence of ASN Digital Competence and Digital Leadership on Public Service Effectiveness with Technology Utilization as a Mediating Variable - Ari Ayuningsih; Yohanita Peti Yuliana (Proceeding of The International Conference on Business and Economics, 2026)
This study aims to analyze the influence of ASN digital competence and digital leadership on public service effectiveness, both directly and indirectly through technology utilization as a mediating variable. The population of this study consists of Aparatur Sipil Negara (ASN) working in Semarang City. A purposive sampling technique was employed with criteria including ASN involved in public service delivery, having a minimum of one year of work experience, actively using digital technology, and willing to participate as respondents. The sample comprised 100 respondents. Primary data were collected through structured questionnaires. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) version 3. The results indicate that ASN digital competence and digital leadership have a positive and significant direct effect on public service effectiveness. Technology utilization also has a positive and significant effect on public service effectiveness. Furthermore, ASN digital competence and digital leadership significantly influence technology utilization. The mediation analysis demonstrates that technology utilization positively and significantly mediates the relationship between ASN digital competence, digital leadership, and public service effectiveness.